Assessment of Financial Stability and Business Expansion of JSC Statoil in the ‎Context of Economic Instability - SAVCHINA, Oksana; BRATANOV, Alexandr; SAVCHINA, Olga; SHCHERBACHENKO, Petr (Journal of Advanced Research in Law and Economics, 2019)
The purpose of this study is to assess the financial stability of one of the largest oil and gas company in Norway – JSC Statoil that has been operating for more than 20 years in Russia, which is an important region for expanding its international activities, and determine the impact of financial risks on business expansion in conditions of the economic instability. To implement the research the authors have collected financial data from the reports of financial results and the balance sheets of the company. They have selected the key performance and solvency indicators in particular among which: gross profit margin, net profit, financial debt, liquidity, turnover rates, etc. In order to determine the risk of insolvency the authors have also used the Springate and Taffler predictive models and econometric modelling for assessing the influence of macroeconomic conjuncture on the company’s performance. This can lead to significant financial loss both for the company itself and for the state as a whole, since Statoil is the largest oil and gas company in Norway. Research results suggest that the management of financial risks at the macro level is a fundamental activity for oil and gas companies, especially for commodity market economies.